Using investor relations to maximize equity valuation - Ryan, Thomas M., 1964- (Wiley finance series., 2005)
A practical guide to proactive investor relations (IR) Investor relations (IR) has traditionally been an administrative function within corporate communications, responsible for disseminating public information and answering investor and media questions.